A Note on Automatic Stabilizers in Austria: Evidence from ITABENA - Helmut Hofer; Tibor Hanappi; Sandra Müllbacher (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
In the Great Recession market income of the households in Austria has been reduced and unemployment increased. In this paper we examine the impact of automatic stabilizers on cushioning such income losses. We use ITABENA, an Austrian tax-benefit model, to analyze how shocks on market income and employment are mitigated by taxes and transfers. In the case of a proportional income shock 46 percent of the shock will be absorbed by automatic stabilizers in Austria. For the unemployment shocks automatic stabilizers absorb 68 percent. Automatic stabilizers increase the redistributive effects of the Austrian tax benefit system. We find that recent changes in the income tax code have almost no impact on the size of automatic stabilizers in Austria.
Keywords: E32; E63; H2; H31; 330; automatic stabilization; microsimulation; tax reforms